Ectopic hidradenitis suppurativa on the forearm following a workout challenge: a case report - Sabharwal, Kennedy; Clarke, Emily; Peña-Robichaux, Venessa (International Journal of Research in Dermatology, 2026)
Hidradenitis suppurativa (HS) typically affects intertriginous areas. Ectopic HS in uncommon locations is rare, often misdiagnosed, and poorly recognized in clinical practice. A 39-year-old African American woman with established Hurley stage III HS in typical locations (axillae, groin, buttocks) presented with a four-week history of a painful lesion on her left forearm. Her HS had been well-controlled on bimekizumab therapy. The ectopic lesion developed following a "plank challenge" workout, appearing at the pressure point where her forearm contacted the ground during planks, suggesting mechanical trauma as the triggering factor. This case represents ectopic HS, occurring in a patient with pre-existing typical HS. The forearm lesion likely resulted from the Koebner phenomenon, where repetitive mechanical trauma and friction led to ectopic HS development. Environmental factors such as secondhand smoke exposure may have contributed to pathogenesis. The lesion responded well to topical medications and intralesional steroid injections. Mechanical trauma can trigger ectopic HS through the Koebner phenomenon in patients with established disease. Physicians should maintain high suspicion for ectopic HS when patients with known HS develop new lesions in atypical locations following trauma or repetitive friction.